The violence of care : rape victims, forensic nurses, and sexual assault intervention - Mulla, Sameena (New York University Press, 2014)
Every year in the U.S., thousands of women and hundreds of men participate in sexual assault forensic examinations. Drawing on four years of participatory research in a Baltimore emergency room, Sameena Mulla reveals the realities of sexual assault response in the forensic age. Taking an approach developed at the intersection of medical and legal anthropology, she analyzes the ways in which nurses work to collect and preserve evidence while addressing the needs of sexual assault victims as patients. Mulla argues that blending the work of care and forensic investigation into a single interventi.